Keeping Identity, Freedom, and Independence of Polish Exiles in Siberia in 19th Century (till 1914). Part II. Ideas on Freedom and Independence - Caban, Wiesław (Respectus Philologicus, 2015)
First Poles were sent to Siberia in the second half of the 18th century; then, after the fall of the November Uprising (1831), about ten thousand young Poles were deported to Siberia. More than twenty thousand people were exiled after the fall of the January Uprising (1863); whereas, the beginning of 1880s saw large deportation of those who were the members of socialist parties. The majority of deportees thought that the time in exile should be devoted to self-education and self-organization; therefore, the necessity to cultivate patriotic sentiments and Catholic religion was unquestionable. Some deportees were strongly convinced that it is not enough to cultivate Polish traditions to get ready for the economic development of Poland, once the independence is regained; thus, it was necessary to take immediate steps that would bring freedom. One of the best known cases of such thinking is the so called Omsk Conspiracy. In 1833, the deportees from the Omsk region came up with a plan for an uprising, another revolt against stardom was planned in 1866 in Transbaikal; however, both of those attempts failed.